Pulmonary Arterial Hypertension Associated With Congenital Heart Disease - Sheikh, Naveen (University Heart Journal, 2017)
The management of patients with congenital heart disease (CHD) and pulmonary arterial hypertension (PAH) has changed dramatically with the development of targeted therapy with selective pulmonary vasodilators. It is important to develop evidence-based guidelines for the management of these patients, and to achieve this, a register of adult Bangladeshi patients with PAH associated with CHD should be established. At the World Symposium in Nice, France, in 2013, the consensus was reached that patients with a pulmonary resistance of < 4 Wood Units (WU)û0m2 have operable disease, and patients with a pulmonary resistanceof > 8 WUû0m2 have inoperable disease. However, these criteria are conservative. Some patients with a pulmonary resistance of > 8 WUû0m2 and a good response to a pulmonary vasodilator test have operable disease and a favorable clinical course long after repair of CHD. The criteria determining operability in patients with PAH associated with CHD in the era of pulmonary vasodilators should be established using data obtained from patient registers and/or multicenter studies. The optimal management of Eisenmenger syndrome should also be established using data obtained from patient registers. Prospective studies should be conducted to determine the life expectancy of patients with Eisenmenger syndrome in the era of targeted therapy. A relatively mild increase in pulmonary resistance may result in failure of a Fontan circulation. The effects of pulmonary vasodilators on the long-term prognosis of patients who have undergone the Fontan operation are still unclear. (Int Heart J 2015; 56: S1-S3). University Heart Journal Vol. 12, No. 1, January 2016; 31-33